Inflammatory Myositis in Cancer Patients Receiving Immune Checkpoint Inhibitors. Issue 5 (1st April 2021) - Aldrich, Jeffrey; Pundole, Xerxes; Tummala, Sudhakar; Palaskas, Nicolas; Andersen, Clark R.; Shoukier, Mahran; Abdel‐Wahab, Noha; Deswal, Anita; Suarez‐Almazor, Maria E.
Abstract : Objective: To estimate the incidence of immune checkpoint inhibitor–related myositis (ICI‐myositis) in cancer patients receiving ICIs, and to report associated clinical manifestations, patterns of care, and outcomes. Methods: We identified a retrospective cohort of patients receiving ICIs between 2016 and 2019 seen at the University of Texas MD Anderson Cancer Center. Cases of ICI‐myositis were identified using International Classification of Disease codes and confirmed by reviewing medical records and pathology, as available. Results: A total of 9, 088 patients received an ICI. Thirty‐six patients (0.40%) were identified as having ICI‐myositis: 17 patients (47%) with ICI‐myositis alone and 19 (53%) with overlap manifestations (5 patients with myocarditis, 5 with myasthenia gravis, and 9 with both). The incidence of ICI‐myositis was 0.31% in those receiving ICI monotherapy and 0.94% in those receiving combination ICI therapy (relative risk 3.1 [95% confidence interval 1.5–6.1]). Twenty‐five patients (69%) received ≥1 treatment in addition to glucocorticoids: plasmapheresis in 17 patients (47%), intravenous immunoglobulin in 12 (33%), and biologics in 11 (31%). Patients with overlap conditions had worse outcomes than those with myositis alone, and 79% of them developed respiratory failure. Eight patients died as a result of ICI‐myositis, and all had overlap syndrome with myasthenia gravis or myocarditis ( P < 0.05); 75% of these patients had a concomitant infection. Conclusion: ICI‐myositis is a rare but severe adverse event. More than half of the patients presented with overlap manifestations and had deleterious outcomes, including respiratory failure and death. None of the patients with ICI‐myositis alone died as a result of adverse events. Optimal treatment strategies have yet to be determined.